Open Ended Approach for Students' Mathematical Creative Thinking Ability - Senita Adelia; Suhar; Saleh (Jurnal Amal Pendidikan, 2024)
The purpose of this study was to determine the effect of open ended approach on students' mathematical creative thinking ability. This research is based on the importance of mathematical creative thinking skills to solve mathematical problems in a more flexible and innovative way, which in turn can develop students' abilities in various aspects of life, both in academic and non-academic fields. This type of research is a quasi-experiment and uses a quantitative approach with a Posttest Only Control Design. The study population included all VIII grade students, using cluster random sampling technique, two classes were obtained, namely class VIII-7 as the experimental class and class VIII-10 as the control class. Data were collected through observation sheets and tests of students' mathematical creative thinking skills. Data analysis was conducted using descriptive and inferential methods. The results of descriptive analysis showed that the average mathematical creative thinking ability of students taught with an open ended approach was 70.89 higher than that of students taught with a scientific approach of 62.57. The results of inferential analysis with Independent Sample T-Test showed sig value. 0,038 < 0,05. The conclusion of this study is that the open ended approach has an influence on students' mathematical creative thinking skills.